Effect of green manures and urea on nitrogen mineralization in relation to growth of rice under Upper Brahmaputra Valley zone of Assam - DEKAMEDHI, B; MEDHI, D N (The Indian Journal of Agricultural Sciences, 2013)
Â An experiment was conducted during 1995 and 1996 at Jorhat to study the nitrogen mieralization and growth of rice treated with green manures, viz Sesbania rqstrata L., Sesbania aculeata L. and urea. Nitrogen was applied @ 40 kg N/ha and ’Lachit’ rice (Oryza satiya L.) was used as the test crop. Incorporation of green manure delayed the release of exchangeable NH4 Â± N than that of urea. Addition of green manure and urea increased grain yield, straw yield and N uptake significantly than the control. More N was retained in the soil from green manure than from urea indicating higher residual effect of green manures.